Dissolution of Platinum Single Crystals in Acidic Medium - Sandbeck, Daniel J.S.; Brummel, Olaf; Mayrhofer, Karl J.J.; Libuda, Jörg; Katsounaros, Ioannis; Cherevko, Serhiy (ChemPhysChem, 2019)
Platinum single crystal basal planes consisting of Pt(111), Pt(100), Pt(110) and reference polycrystalline platinum Pt(poly) were subjected to various potentiodynamic and potentiostatic electrochemical treatments in 0.1 M HClO4. Using the scanning flow cell coupled to an inductively coupled plasma mass spectrometer (SFC-ICP-MS) the transient dissolution was detected on-line. Clear trends in dissolution onset potentials and quantities emerged which can be related to the differences in the crystal plane surface structure energies and coordination. Pt(111) is observed to have a higher dissolution onset potential while the generalized trend in dissolution rates and quantities was found to be Pt(110)>P(100)≈Pt(poly)>Pt(111).
CRIS-Team Scopus Importer:2019-11-19
Keywords: fuel cells; platinum; platinum dissolution; platinum single crystals; stability